Edukasi dan Skrining Penyakit Cacingan pada Siswa SDN 10 Kelurahan Lambung Bukit - Eka Nofita; Hasmiwati Hasmiwati; Adrial Adrial; Nurhayati Nurhayati; Selfi Renita Rusjdi; Husnil Wardiyah; Nuzulia Irawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2022)
One of the primary health problems still found in Lambung Bukit Village is the high stunting rate. The incidence of stunting is influenced by many factors, one of which is intestinal worm infection (Helminthiasis). Worms that live in the intestine will interfere with the absorption of food and suck the blood of their host, causing malabsorption, malnutrition and growth disorders, which can cause stunting. Therefore, genuine efforts are needed to eradicate this helminthic disease. Department Parasitology of Medical Faculty, the Andalas University, conducted community service activities at SDN 10 Lambung Bukit to reduce intestinal worm infections in children by providing counselling, detection and treatment, and follow-up on treatment success. The counselling activity was attended by 88 students and eight teachers, with 59 samples of faeces collected. From the stool examination results, none of the worm eggs was found, but four students were positive for intestinal protozoa. Furthermore, treatment was given to these four students. Through this activity, it was expected to increase students' awareness of maintaining personal hygiene so that to reduce the incidence of helminthiasis, and help to reduce stunting rates.